Prevalence of amyloid and positive Congo red frequency among routine surgical specimens. (2nd July 2016) - Pilley, Jacob; Lane, Jason; Ravichandran, Pars
Abstract : Amyloidosis is characterized by an extracellular tissue deposition of one of a family of biochemical proteins that are abnormally folded. The deposits are often subtle, and can be missed on routine hematoxylin and eosin (H&E)-stained slides. Current literature does not offer an expected prevalence rate of amyloid or frequency of Congo red positivity among routine surgical pathology specimens in a referral bias-free setting. The objective of this study was to determine these parameters at a large community hospital. The pathology database was searched for all surgical pathology and autopsy cases diagnosed with amyloidosis from 2001–2013. All cases were reviewed and clinical parameters were recorded. Based on H&E interpretation, Congo red was performed on 218 cases. Of these, 36% confirmed positive birefringence. The prevalence of amyloid among routinely submitted pathology specimens was calculated as 0.027% over the 13-year interval. Amyloid was detected in less than 1% of routine surgical specimens. When suspicious H&E findings prompted Congo red staining, amyloidosis was confirmed about a third of the time over the 13-year period. Establishing an optimal rate of Congo red utilization may provide a standard measurement needed to ensure high amyloid detection rates among pathologists at the community level.